Chromatic pupillometry for evaluating melanopsin retinal ganglion cell function in Alzheimer’s disease and other neurodegenerative disorders: a review - Romagnoli, Martina; Amore, Giulia; Avanzini, Pietro; Carelli, Valerio; La Morgia, Chiara (Frontiers in Psychology, 2024)
The evaluation of pupillary light reflex (PLR) by chromatic pupillometry may provide a unique insight into specific photoreceptor functions. Chromatic pupillometry refers to evaluating PLR to different wavelengths and intensities of light in order to differentiate outer/inner retinal photoreceptor-contributions to the PLR. Different protocols have been tested and now established to assess in-vivo PLR contribution mediated by melanopsin retinal ganglion cells (mRGCs). These intrinsically photosensitive photoreceptors modulate the non-image forming functions of the eye, which are mainly the circadian photoentrainment and PLR, via projections to the hypothalamic suprachiasmatic and olivary pretectal nucleus, respectively. In this context, chromatic pupillometry has been used as an alternative and noninvasive tool to evaluate mRGC-system in several clinical settings, including hereditary optic neuropathies, glaucoma and neurodegenerative disorders like Parkinson’s disease (PD), idiopathic/isolated rapid eye movement sleep behavior disorder (iRBD) and Alzheimer’s disease (AD). The purpose of this manuscript is to review the key steps of chromatic pupillometry protocols for studying in-vivo mRGC-system functionality and provide the main findings of this technique in the research setting on neurodegeneration. mRGC-dependent pupillary responses are short-wavelength sensitive, have a higher threshold of activation and are much slower and sustained compared with rod- and cone-mediated responses, driving the tonic component of the PLR during exposure to high-irradiance and continuous light stimulus. Thus, mRGCs contribute mainly to the tonic component of the post-illumination pupil response (PIPR) to bright blue light flash that persists after light stimulation is switched off. Given the role of mRGCs in circadian photoentrainment, their functional evaluation by using chromatic pupillometry may be proposed as an early biomarker of mRGC-dysfunction in neurodegenerative disorders characterized by circadian and/or sleep dysfunction such as AD, PD and its prodromal phase, iRBD. The evaluation by chromatic pupillometry of mRGC-system functionality may lay the groundwork for a new, easily accessible biomarker that can be exploited also as the starting point for future longitudinal cohort studies aimed at stratifying the risk of conversion in these disorders.